2010
DOI: 10.1055/s-0029-1243230
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Insulin Detemir and Insulin Glargine on Glycemic Variability in Patients with Type 1 and Type 2 Diabetes

Abstract: The present study demonstrated lower within-subject variability of insulin detemir compared to insulin glargine, suggesting that the basal insulin replacement with insulin detemir may provide a useful therapeutic strategy for uncontrolled type 1 diabetes with high glucose variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
3
9
0
Order By: Relevance
“…As titration in this study was at the treating physicians’ discretion, the difference in the incidence of hypoglycaemia in favour of the insulin detemir group may be partly because of the varying up-titration between the two groups and the slightly higher HbA 1c values at final visit (7.48% vs. 7.38%) in patients treated with insulin detemir. However, reduced intra-patient glucose variability seen in patients treated with insulin detemir may also play a role [29-31]. Unlike some of the previous randomised controlled trials, where final insulin dose was found to be greater for insulin detemir compared with insulin glargine at the final visit [21-23], our data indicate similar end-of-study dose values between the two insulin analogues.…”
Section: Discussionsupporting
confidence: 47%
“…As titration in this study was at the treating physicians’ discretion, the difference in the incidence of hypoglycaemia in favour of the insulin detemir group may be partly because of the varying up-titration between the two groups and the slightly higher HbA 1c values at final visit (7.48% vs. 7.38%) in patients treated with insulin detemir. However, reduced intra-patient glucose variability seen in patients treated with insulin detemir may also play a role [29-31]. Unlike some of the previous randomised controlled trials, where final insulin dose was found to be greater for insulin detemir compared with insulin glargine at the final visit [21-23], our data indicate similar end-of-study dose values between the two insulin analogues.…”
Section: Discussionsupporting
confidence: 47%
“…1). Lower variability of insulin detemir has also been demonstrated in several clinical studies of patients with DM [44,45].…”
Section: Glycemic Variability Hypoglycemic Risk and Pregnancy Outcomesmentioning
confidence: 73%
“…In a cross-over study, Tone et al had 15 Type 1 diabetic and 14 Type 2 diabetic patients on intensive insulin treatment who were switched from insulin detemir to insulin glargine or from insulin glargine to insulin detemir as the basal insulin and evaluated changes in glycemic variability with standard deviation and coefficient of variance of capillary glucose values. They found a beneficial effect of switching insulin glargine to insulin detemir in Type 1 diabetic patients who had high glycemic variability (20). However, Renard et al reported that insulin glargine had not weaker effect than did insulin determir according to the coefficient of variation and fasting blood glucose levels in their multicenter, randomized study with a 16-week crossover period on 78 Type 1 diabetic patients (21).…”
Section: Discussionmentioning
confidence: 98%